Returns to Higher Education - Graduate and Discipline Premiums - Yu Zhu; Lei Xu (Global Labor Organization (GLO), 2022)
This chapter reviews and evaluates progress in recent research on the graduate premium in general as well as the differential graduate premiums by discipline, accounting for higher-education choice by individuals under substantial uncertainty. The contribution of this review, relative to previous reviews, is the collection of a wider variety of evidence that all bears on a relatively narrow issue, namely the graduate and discipline premiums, allowing for selection into undergraduate degree and degree subjects which include the option value of undertaking postgraduate degrees. The issue of subject-job match quality after graduation is only treated as a sensitivity check to the main results, due to concerns with self-selection. To avoid overlap with the more thematic chapters in this handbook which focus on HE structures and student financing respectively, this review only emphasizes that the sizes of the graduate and discipline premiums are context-specific, especially regarding how HE is structured and financed in a country, without going into details. Much higher weight is placed on the most up-to-date research that sheds light on the causal effects of higher-education and subject choice, and the conclusions are heavily driven by the best evidence rather than by consensus built around correlations. The chapter ends with a short summary of the empirical evidence and a brief discussion of possible areas for future research.
Keywords: I26; I23; I24; 330; graduate premium; discipline premiums; higher-education choice; subject-job match; causal effects